2019
DOI: 10.1158/1078-0432.ccr-18-3034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biomarker Assays for EGFR: Implications for Precision Medicine in Patients with Glioblastoma

Abstract: Purpose: Patients with glioblastoma (GBM) have a poor prognosis and are in desperate need of better therapies. As therapeutic decisions are increasingly guided by biomarkers, and EGFR abnormalities are common in GBM, thus representing a potential therapeutic target, we systematically evaluated methods of assessing EGFR amplification by multiple assays. Specifically, we evaluated correlation among fluorescence in situ hybridization (FISH), a standard assay for detecting EGFR amplification, with other methods. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The first cluster (C1) offers a low rate of SCNAs compared with the rest. Cluster 2 (C2) and cluster 3 (C3) share a high rate of SCNAs in MTAP, CDKN2A, MSH6 and EGFR, in agreement with previous descriptions [16], and suggesting that GBs from both clusters display alterations in DNA metabolic processes (by STRING). However, the second cluster (C2) concentrates the co-existence of EGFR alterations through EGFRvIII or EGFR amplification and the highest rate of SCNAs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The first cluster (C1) offers a low rate of SCNAs compared with the rest. Cluster 2 (C2) and cluster 3 (C3) share a high rate of SCNAs in MTAP, CDKN2A, MSH6 and EGFR, in agreement with previous descriptions [16], and suggesting that GBs from both clusters display alterations in DNA metabolic processes (by STRING). However, the second cluster (C2) concentrates the co-existence of EGFR alterations through EGFRvIII or EGFR amplification and the highest rate of SCNAs.…”
Section: Discussionsupporting
confidence: 90%
“…STRING analysis correlates the SCNA statistically associated with amplified-EGFR GBs with NOTCH3 activation and negative regulation of cell-matrix adhesion. Crespo et al, using high-density (500K) single-nucleotide polymorphism arrays, achieved similar relevance for the axis established with MTAP [16]. In concordance with that work, our group of patients that displayed EGFRvIII, which is the one with the worst outcome, also showed the impairment of cell-matrix adhesion processes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In recent years, accumulated evidence suggested that amplification of the EGFR and other genes might play a critical role in the oncogenesis and clinical behavior of GBM [22,26,27]. Despite this, with the exception of a recent study [28], no clear association has been reported in the literature between the GEP and the genetic alterations of individual genes in GBM [29]. In order to investigate the potential association between overexpression of EGFR, CDK4, MDM4, and PDGFRA, subsequent analysis of gene amplification was performed at the DNA level.…”
Section: Discussionmentioning
confidence: 98%